ANALISIS PEMETAAN ZONA PENANGKAPAN IKAN TONGKOL (Euthynnus affinis) PADA PERAIRAN TELUK BANTEN DAN SEKITARNYA - Zoldha Adra Maulidha Purnama, - (2022)
In Banten Bay and the surrounding waters there are various types of fish caught. In the implementation of this research, the aim is to determine and map the potential fishing zone of tuna (Euthynnus affinis) in July to December, which is the transition season from dry to rainy from 2019 to 2021. In practice the method used is using Aqua MODIS Satellite Imagery. namely Sea Surface Temperature and Chlorophyll-a. The results showed that there were fluctuating changes in terms of SST, chlorophyll and points suspected to be potential zones for catching tuna (Euthynnus affinis). In the waters of Banten Bay and its surroundings, the average chlorophyll-a concentration value is in the range of 0.5 mg/L to 1.54 mg/L for the last three years, namely 2019 to 2021. In the value of Sea Surface Temperature (SST) there are various changes in both increase and decrease in temperature over the last three years, the highest SST is 33.31oC occurring in September 2021 and the lowest SST is in November in 2020 which is 27.84oC. Location of the potential zone for tuna fishing (Euthynnus affinis) found at coordinates between 106°00'8.00"E to 106°35'80.00"E and 5°60'90.00"LS to 5°96'00.00" South Latitude with predictions of the abundance of fishing points in October, which is 56 points.